African swine fever; insights into genomic aspects, reservoirs and transmission patterns of virus - Alotaibi, Bader S.; Wu, Chia-Hung; Khan, Majid; Nawaz, Mohsin; Chen, Chien-Chin; Ali, Abid (Frontiers in Veterinary Science, 2024)
African swine fever is a hemorrhagic disease of pigs with high mortality rates. Since its first characterization in 1921, there has been sufficient information about African swine fever virus (ASFV) and related diseases. The virus has been found and maintained in the sylvatic cycle involving ticks and domestic and wild boars in affected regions. The ASFV is spread through direct and indirect contact with infected pigs, their products and carrier vectors especially Ornithodoros ticks. Severe economic losses and a decline in pig production have been observed in ASFV affected countries, particularly in sub-Saharan Africa and Europe. At the end of 2018, the ASFV adversely affected China, the world's leading pork-producer. Control strategies for the disease remained challenging due to the unavailability of effective vaccines and the lack of successful therapeutic measures. However, considerable efforts have been made in recent years to understand the biology of the virus, surveillance and effective control measures. This review emphasizes and summarizes the current state of information regarding the knowledge of aetiology, epidemiology, transmission, and vaccine-based control measures against ASFV.